Representações sociais da gestão escolar sobre tecnologia assistiva na escolarização da pessoa com deficiência em comunidades tradicionais no Nordeste Paraense - OLIVEIRA, Mequias Pereira de (2022)
This investigation aims to analyze the social representations of school management on the use of Assistive Technology in the schooling of DWP in Traditional Communities in Northeast Para. The qualitative approach was applied (CHIZZOTTI, 2006) with an application of open questionnaires (SEVERINO, 2007). Six managers and five coordinators participated in this research of four schools from Municipal Education Network located in Traditional Communities surrounding the Marine Extractive Reserve Caete-Taperaçu, in Bragança-PA. The content analysis was used in the treatment of data (BARDIN, 2016), and the interpretation was anchored in the assumptions of the Social Representation Theory (MOSCOVICI, 1978, 2015). The discussion was involved dialogue between authors from School Management, Assistive Technology, and documents from the National Policy on Special Education. In Traditional Communities, School Management represents Assistive Technology as pedagogical resources that promote accessibility and contribute to the socio-school development of DWP. The resources include educational games, computers, software, magnifying glasses, Libras (Brazilian Sign Language) panel, Braille pedagogical materials (geometric shapes, alphabets, and syllabaries), data show, and television in the participant conception. Disable people are subject to rights and must access school education according to the perspective of coordinators and managers. The pedagogical and administrative strategies can boost school inclusion through project construction, collective work, acquisition of Assistive Technology, continuing training for teachers, financial resources and their appropriate use, compliance with standards, enrollments guarantee, referral of the DWP to specialized centres for evaluation, with the infrastructure modifications, and the legislation implementation current on the school inclusion of the DWP. This research showed that Assistive Technology and DWP inclusion are not synonymous. It is just one of the alternatives that can contribute. The paper concludes that Assistive Technology is not a foreign subject to School Management work. However, training education is a need in schools, for greater clarification of professionals and better guidance for DWP regarding its use. Thus, social representations its origin in the context of Special Education based on the relationships established with the DWP through participation in the school spaces, the procedures, the professionals involved, and the resources used.